Teacher Spirituality Assessment in Developing Character-Oriented Educators: A Systematic Literature Review - Muwaffaq, Abdullah; Usman, Errina; Irwanto, Moch. Surya Hakim; Siswoyo, Selina Rahmawati; Aswati, Ani Tuti; Maulana, Hamdu; Masor, Satiya (Jurnal Tarbiyatuna, 2025)
This study aims to systematically review the literature on teacher spirituality assessment and its role in developing character-oriented educators. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant articles published between 2020 and 2025 were retrieved from Scopus and Google Scholar and selected through identification, screening, eligibility, and inclusion stages. The analysis reveals that teacher spirituality assessment plays a crucial role in supporting the formation of teachers”™ professional character. Four core dimensions of teacher spirituality grounded in the Qur”™anic perspective were consistently identified across the literature: hablum minallah (relationship with God), hablum minan naas (relationship with others), hablum minal alam (relationship with nature), and hablum minan nafs (relationship with oneself). These dimensions highlight that teacher character development is closely linked to spiritual awareness that integrates personal, social, environmental, and transcendental aspects. The findings suggest that spirituality assessment should be implemented as a continuous and reflective process to support sustainable character education among teachers. This review provides a conceptual foundation for developing contextually relevant teacher spirituality assessment frameworks in educational settings.